Ectopic corticotropin-releasing hormone (CRH) syndrome from metastatic small cell carcinoma: a case report and review of the literature - Shahani Sadeka; Nudelman Rodolfo J; Nalini Ramaswami; Kim Han-Seob; Samson Susan L (BMC, 2010)
Abstract Background Cushing's Syndrome (CS) which is caused by isolated Corticotropin-releasing hormone (CRH) production, rather than adrenocorticotropin (ACTH) production, is extremely rare. Methods We describe the clinical presentation, course, laboratory values and pathologic findings of a patient with isolated ectopic CRH causing CS. We review the literature of the types of tumors associated with this unusual syndrome and the behavior of these tumors by endocrine testing. Results A 56 year old woman presented with clinical and laboratory features consistent with ACTH-dependent CS. Pituitary imaging was normal and cortisol did not suppress with a high dose dexamethasone test, consistent with a diagnosis of ectopic ACTH. CT imaging did not reveal any discrete lung lesions but there were mediastinal and abdominal lymphadenopathy and multiple liver lesions suspicious for metastatic disease. Laboratory testing was positive for elevated serum carcinoembryonic antigen and the neuroendocrine marker chromogranin A. Serum markers of carcinoid, medullary thyroid carcinoma, and pheochromocytoma were in the normal range. Because the primary tumor could not be identified by imaging, biopsy of the presumed metastatic liver lesions was performed. Immunohistochemistry was consistent with a neuroendocrine tumor, specifically small cell carcinoma. Immunostaining for ACTH was negative but was strongly positive for CRH and laboratory testing revealed a plasma CRH of 10 pg/ml (normal 0 to 10 pg/ml) which should have been suppressed in the presence of high cortisol. Conclusions This case illustrates the importance of considering the ectopic production of CRH in the differential diagnosis for presentations of ACTH-dependent Cushing's Syndrome.